ANALISIS KEBIJAKAN KREDIT TERHADAP EFEKTIVITAS PENGUMPULAN PIUTANG DI BALI GARDEN HOTEL - Ketut Sudarsana, SS., MM. (Institut Pariwisata dan Bisnis Internasional, 2014)
Hotels do credit sales to increase sales , but also should consider about credit terms and also how the path should be taken in the collection of accounts receivable policy . This has often times become a problem in the process of collecting receivables where companies only consider one or two things that a strength of the debtor or loan recipient . The slow turnover rate and the amount of the accounts receivable average collection of accounts receivable could be due to the credit policies applied by the Bali Garden Hotel is less efektif.Pokok problem of this study is the extent to which the effectiveness of credit policy should be set out in the Bali Garden Hotel ?To avoid widespread discussion of the subject matter , the study was limited to the collection of accounts receivable credit policy of the travel agent . While other accounts not examined.The results of the analysis of the results obtained credit policies established by the management of Bali Garden Hotel , has not been properly implemented . This can be evidenced from the few things that still deviate from established procedures and theories associated with the credit policy . Credit analysis has been done on the discussions , the collection of accounts receivable that will take place in Bali Garden Hotel is not effective because it does not meet the standards set . This is evidenced by some of the quantitative analysis is relevant in calculating the effectiveness of the collection of accounts receivable at the Bali Garden Hotel , namely : Turn Over Accounts Receivable, Accounts Receivable Average Collection Period, and Accounts Receivable as Percentage of Revenue.Â